Safe Trajectory Planning for Maritime Surface Ships - Lazarowska, Agnieszka (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book offers a comprehensive review of collision avoidance techniques and safe trajectory planning for manned and unmanned ships, together with extensive information on how to develop and implement algorithms for applications in real-world settings. It describes the most relevant decision-support systems and guidance systems used in the control of marine craft, giving a special emphasis to autonomous vehicles, but also covering manned ones. Thanks to its good balance of theory and practice, and the inclusion of basic explanations of all essential concepts, this book fills an important gap in the literature of marine navigation, providing not only researchers and practitioners with a timely reference guide to safe trajectory planning, but also supporting students and newcomers to the field.
Introduction -- Problem definition -- Methodology for safe trajectory planning -- Deterministic algorithms -- Non-deterministic algorithms -- Registration of navigational data -- Evaluation of algorithms.
Keywords: Control engineering; Marine engineering; Machine learning; Robotics; Control and Systems Theory; Marine Engineering; Machine Learning; Robotic Engineering